Halichoerus grypus subsp. grypus Fabricius 1791 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Halichoerus grypus subsp. grypus Fabricius 1791 Halichoerus grypus subsp. grypus Fabricius 1791, Skr. Nat. Selsk. Copenhagen, 1 (2): 167. Type Locality: Listed by Scheffer (1958) as " Greenland ". Synonyms: Halichoerus grypus subsp. atlantica Nehring 1886; Halichoerus grypus subsp. griseus Nilsson 1820. Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Carnivora, pp. 532-628 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 596, DOI: 10.5281/zenodo.7316519